1996
DOI: 10.1093/oxfordjournals.jleo.a023360
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants and Impact of Property Rights: Land Titles on the Brazilian Frontier

Abstract: We give special thanks to the research assistance and comments provided by James Dalen, Jr., Jeffrey Fuller, Bernardo Mueller, and Ricardo Tarifa. We benefitted from lengthy comments provided by Ron Oaxaca and Pablo Spiller. We also received helpful suggestions from Ann Carlos, Linda Cohen, Gershon Feder, Price Fishback, Doc Ghose, Shawn Kantor, Larry Neal, Barbara Sands, Leslie Stratton, Les Taylor, the referees, and participants at seminars at Clemson University; University of California-Berkeley; University… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
120
0
14

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 322 publications
(140 citation statements)
references
References 27 publications
2
120
0
14
Order By: Relevance
“…l Forests Empirical research using cross-country data to explore the government-related causes of deforestation in particular has grown rapidly since the early 1990s. Earlier case study research found that weak property rights were associated with loss of forest cover (Gillis 1980;Repetto & Gillis 1988;Vincent 1990;Southgate et al 1991;Alston et al 1996;Godoy et al 1996;Pinchon 1997). Using panel data, cross national studies substantiated this claim (Deacon 1994(Deacon , 1999Bohn & Deacon 2000).…”
Section: R Smith Et Al Use National Level Indicators Of Corruption mentioning
confidence: 99%
“…l Forests Empirical research using cross-country data to explore the government-related causes of deforestation in particular has grown rapidly since the early 1990s. Earlier case study research found that weak property rights were associated with loss of forest cover (Gillis 1980;Repetto & Gillis 1988;Vincent 1990;Southgate et al 1991;Alston et al 1996;Godoy et al 1996;Pinchon 1997). Using panel data, cross national studies substantiated this claim (Deacon 1994(Deacon , 1999Bohn & Deacon 2000).…”
Section: R Smith Et Al Use National Level Indicators Of Corruption mentioning
confidence: 99%
“…A partial listing includes Jimenez (1984), Alston et al (1996) and Lanjouw and Levy (2002) on real estate values; Besley (1995), Brasselle et al (2002), Field (2005), and Do and Iyer (2008) on investment; Banerjee et al (2002) and Libecap and Lueck (2008) on agricultural productivity, Field (2007) on labor supply; Feder et al (1988), Place and Migot-Adholla (1998), Carter and Olinto (2002), Field and Torero (2003) on access to credit, and Di Tella, Galiani and Schargrodsky (2007) on the formation of beliefs. Our strong results on investment and our weak results on access to credit coincide with the findings of this preceding literature.…”
Section: Introductionmentioning
confidence: 99%
“…(1991), and Carter, Wiebe and Blarel (1994). It is formalized in Alston, Libecap and Schneider (1996) who interact title with distance from a market in land value estimations; and in Carter and Olinto (1996) who allow household characteristics to influence credit constraints in a multiple equation model of investment. The latter emphasize that household characteristics, notably wealth, may affect the value of title (and they estimate a positive interaction).…”
mentioning
confidence: 99%